STRATEGI DAN MEKANISME PEMBINAAN PRANIKAH OLEH KANTOR URUSAN AGAMA KECAMATAN PONTIANAK BARAT DI MASA PANDEMI COVID-19 - Atikah, Siti; Marluwi, Marluwi; Wibowo, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The purpose of the study was to find out the strategies given to prospective brides regarding BP4 premarital guidance during the covid-19 pandemic and to find out the mechanism given to prospective brides by KUA officers during the covid-19 pandemic.This research includes field research that uses an empirical normative approach that is descriptive qualitative. The research subjects are the supervisors in the KUA environment, namely the Penghulu as well as extension workers at the KUA, West Pontianak District. Then the data sources which is researchers used for this study were primary data sources, namely direct data from the subject and secondary data sources, namely data from books, journals, and other data. The techniques used by researchers in this study are interviews, documentation and observation. In the data analysis technique for this research, namely reducing presenting, and finally drawing conclusions. Furthermore, from data sources to research techniques, the researchers then checked the validity of the data in order to prevent fraud or lies. Based on the results of the research obtained by the researchers, it can be concluded that the delivery of premarital coaching during the covid-19 pandemic by BP4 KUA West Pontianak District has been running optimally and smoothly. 1). The strategy for pre-marital coaching during the covid-19 pandemic by BP4 KUA West Pontianak District was carried out using only two strategies, namely the delivery strategy before the marriage contract and the delivery strategy when the bride and groom came to the KUA to provide marriage documents. We use this submission to provide pre-marital coaching with the lecture method and interview method. 2). Regarding the mechanism provided for prospective brides and the public, namely online or offline. But most brides choose to go offline rather than online while maintaining health protocols as well, the material provided by the bride and groom at the time of pre-wedding marriage is a) becoming a sakinah mawaddah warahmah family that is expected by the bride and groom, b) meeting the family's needs physically and mentally. , c) maintain reproductive health, d) prepare a quality generation, and e) resolve conflicts in the household.